(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The experience of countries around the world shows that the active attraction of foreign investments to the country’s economy is one of the important factors in ensuring economic development. This issue, first of all, depends on the investment attractiveness of the country, the conditions created for foreign investors and the investment policy pursued in the country. In turn, the active attraction of foreign investments to the country’s economy creates opportunities for further socio-economic development of the country and ensuring the well-being of the population, implementing structural changes in production and its intensive development, introducing modern technologies in the sectors of the economy to produce competitive products, high-tech production for deep processing of mineral raw materials and agricultural resources, and increasing the country’s export potential. "Ensuring such an opportunity and the effectiveness of economic and social reforms aimed at achieving it directly depend on the extent and form of their attraction.